Chromatic mechanisms in striate cortex of macaque - Lennie, P (J Neurosci, 1990)
We measured the responses of 305 neurons in striate cortex to moving sinusoidal gratings modulated in chromaticity and luminance about a fixed white point. Stimuli were represented in a 3-dimensional color space defined by 2 chromatic axes and a third along which luminance varied. With rare exceptions the chromatic properties of cortical neurons were well described by a linear model in which the response of a cell is proportional to the sum (for complex cells, the rectified sum) of the signals from the 3 classes of cones. For each cell there is a vector passing through the white point along which modulation gives rise to a maximal response. The elevation (theta m) and azimuth (phi m) of this vector fully describe the chromatic properties of the cell. The linear model also describes neurons in l.g.n. (Derrington et al., 1984), so most neurons in striate cortex have the same chromatic selectivity as do neurons in l.g.n. However, the distributions of preferred vectors differed in cortex and l.g.n.: Most cortical neurons preferred modulation along vectors lying close to the achromatic axis and those showing overt chromatic opponency did not fall into the clearly defined chromatic groups seen in l.g.n. The neurons most responsive to chromatic modulation (found mainly in layers IVA, IVC beta, and VI) had poor orientation selectivity, and responded to chromatic modulation of a spatially uniform field at least as well as they did to any grating. We encountered neurons with band-pass spatial selectivity for chromatically modulated stimuli in layers II/III and VI. Most had complex receptive fields. Neurons in layer II/III did not fall into distinct groups according to their chromatic sensitivities, and the chromatic properties of neurons known to lie within regions rich in cytochrome oxidase appeared no different from those of neurons in the interstices. Six neurons, all of which resembled simple cells, showed unusually sharp chromatic selectivity.